SIFAT VENIR DAN KAYU LAPIS LIMA JENIS KAYU HUTAN TANAMAN INDUSTRI - Memed Rozak; M I Iskandar; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Five Indonesian wood species were investigated for their veneer and plywood properties. These species include are meranti merah (Shorea stenoptera Burck.), akasia (Acacia magnium Willd.), ampupu T (Eucalyptus urophylla), ampupu A (Eucalyptus urophylla) and ekaliptus (Eucalvptus platiphvlla F.v.M). . Four wood species were peeled in cold condition. Only ekaliptus was found unsuitable for peelling due to high density and the interwoven nature of the fibers. Veneer of 1.5 mm thickness could be produced satistactorily at a cutting angle between 90o92°. Average shrinkage of the veneer is 8.28%. Average swelling from oven dry condition to completely saturabed is 3.76%. Water resistance bonding strength for all wood species studied was m conformity with the Indonesian, Japanese, and German standards. Average thickness reduction due to pressing pressure during plywood making is 0,24 mm. .Average specific gravity of the plywood appeared to 0.048 be percent higher than that of the wood from which they are made of.